Examining the Role of Race and Gender as Moderators of the Relationship Between Depressive Symptoms and Hazardous Alcohol Consumption among DUI Offenders. Issue 2 (4th March 2019) - Tatch, Andrew; Hakki Yigit, Ismail; Brown, Dustin; Robertson, Angela
Abstract: Research consistently documents a positive association between depressive symptoms and hazardous drinking. Fewer studies have examined this relationship among high-risk populations such as Driving Under the Influence (DUI) offenders and rarely evaluate whether the association between depression and hazardous drinking varies by race and gender. We examined the relationship between depressive symptoms and hazardous drinking in a diverse sample of DUI offenders, extending previous research by examining the moderating effects of race and gender. We analyzed survey data collected from DUI offenders ( N  = 10, 082) enrolled in the 2012 Mississippi Alcohol and Safety Education Program. We estimated a series of nested regression models to assess the relationship between depressive symptoms and hazardous drinking. The analyses also assessed the extent to which the hypothesized association between depression symptomology and hazardous drinking varied by race and gender. We documented a positive association between depressive symptoms and hazardous drinking among DUI offenders. The association between depressive symptoms and hazardous drinking was stronger for black offenders relative to white. We found no significant differences by gender. The incorporation of culturally specific needs of DUI offenders may help intervention efforts more efficiently reduce negative consequences associated with impaired driving.